2015
DOI: 10.1111/joic.12203
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Bifurcation Intervention: What Role Do Bifurcation Angles Play?

Abstract: Bifurcation angles play an important role in coronary bifurcation intervention. Bifurcation angles affect the coronary bifurcation intervention from many aspects: (1) impact the atherosclerosis proliferation via affecting the hemodynamic parameters at bifurcation regions; (2) impact side branch compromise after main vessel stenting via hemodynamics, atherosclerosis proliferation, geometric characteristics, and plaque/carina shift; (3) affect the long-term clinical outcome after coronary bifurcation stenting. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…This leads to potential inter-observer and intra-observer variance. Systematic measurement of bifurcation angles should be performed at end systole and end diastole to achieve more accurate and reproducible results [33]. Despite these limitations, a recent study has shown good correlation between CCTA and invasive coronary angiography using bifurcation angle measurements as a criterion to determine coronary stenosis [34].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to potential inter-observer and intra-observer variance. Systematic measurement of bifurcation angles should be performed at end systole and end diastole to achieve more accurate and reproducible results [33]. Despite these limitations, a recent study has shown good correlation between CCTA and invasive coronary angiography using bifurcation angle measurements as a criterion to determine coronary stenosis [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, the bifurcation angle could not predict the need for side branch treatment. 9,13,14 The POC represents the zone of confluence of the distal left main, ostial LAD and ostial LCX arteries. Kang et al concluded mean lumen area (MLA) within the POC may serve as a predictor of stenosis in LM disease.…”
Section: Analysis Of Possible Predictors For Side Branch Treatmentmentioning
confidence: 99%
“…However, POC was unable to predict side branch stenosis requiring the implantation of a second stent. [4][5][6][7][8][9][10][11][12][13][14][15] Studies have shown a greater SYNTAX score in patients undergoing the two-stent strategy than in the one-stent strategy in the indication of angiographic complexity in the two treatment groups. Patients in our study included patients at intermediate risk as the mean SYNTAX score was 26.7±3.7 (21-39).…”
Section: Analysis Of Possible Predictors For Side Branch Treatmentmentioning
confidence: 99%
“…Stenting the parent vessel with provisional stenting of the side branch remains a superior strategy. However, others would suggest that the bifurcation angle is an important determinant of MACE and should be strongly considered before determining the appropriate revascularization strategy …”
Section: Bifurcationsmentioning
confidence: 99%